2009
DOI: 10.12693/aphyspola.115.1101
|View full text |Cite
|
Sign up to set email alerts
|

Performances of Nanosecond Pulsed Discharge

Abstract: The conventional methods such as selective catalytic reduction method, electron beam method and lime--gypsum method could not treat exhaust gases completely. In addition, the energy efficiency and the cost of the conventional ways are still unfavourable. In recent years, the pollution control techniques using electric discharge plasmas which attract attention as the low cost and high energy efficient exhaust gas treatment methods, have been widely studied. In our laboratory, pulsed streamer discharge plasmas w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The difficulty with 5 ns discharge is working at increased ozone concentrations. Figure 29 shows the dependence of O 3 yield on O 3 concentration for different pulse discharge durations [89].…”
Section: Ozone Generationmentioning
confidence: 99%
“…The difficulty with 5 ns discharge is working at increased ozone concentrations. Figure 29 shows the dependence of O 3 yield on O 3 concentration for different pulse discharge durations [89].…”
Section: Ozone Generationmentioning
confidence: 99%
“…The theoretical efficiencies for the production of oxygen radicals and ozone by barrier discharges ignited by sinusoidal or microsecond range pulsed voltages remain in the range of 200-250 g kWh −1 in pure oxygen [67,93] and 100-110 g kWh −1 in dry air. The efficiency may increase up to 500 g kWh −1 and 200 g kWh −1 for pure oxygen and air with the use of nanosecond pulsed discharges [35]. The stoichiometric amount of ozone which is required for the oxidation of NO to NO 2 and N 2 O 5 are respectively 1 and 1.5 times the concentration of inlet NO.…”
Section: Theoretical Efficiency Of O Radical Production and Nomentioning
confidence: 99%
“…The use of plasma additionally allows the oxidation of NO 2 to N 2 O 5 which is beneficial for absorption based methods. Studies carried out by different research groups have shown that it is possible to oxidize all NO to NO 2 when inlet NO concentration is up to of 200-330 ppm depending on experimental conditions [30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The input energy (SIE) required to remove all NO at 200 ppm inlet NO concentration varied from 20 to 200 J l −1 depending on gas composition and reactor temperature [33,36,39,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] It is already reported that a nanosecond pulsed generator that can output 5 ns pulsed voltage was developed for use in exhaust gas treatment and ozone production. [17][18][19][20][21][22][23] In refs. 17-23, it was indicated that the 5 ns pulsed discharge has great advantage in terms of energy efficiency for NO removal and ozone generation over conventional discharge methods.…”
Section: Introductionmentioning
confidence: 99%